Crown margin design and the marginal strength of multilayered zirconia: A step towards clinical relevance using the hoop-strength approach - Lohbauer, Ulrich; Mayer, Johannes; Schwamberger, L.; Belli, Renan; Wartzack, Sandro (Dental Materials, 2025)
Objectives A demand for clinically relevant assessment of materials has been claimed mandatory for better understanding clinical design issues over pure material behavior. Here we focus on a strength test on dome-like half-spheres which serves to simulate the marginal fracture type in single crowns. On the example of a multilayer chairside zirconia material, we aimed to investigate the influence of cervical margin design on crown strength, thereby correlating numeric stress analysis with experimental strength testing assisted by fractographic post-processing. Materials and methods Ninety dome-like half-spheres were CAD/CAM manufactured in a chairside milling unit (PrimeMill, DentsplySirona) using a 4/5Y-PSZ zirconia multilayer chairside block (e.max ZirCAD MT Multi; Ivoclar). Three design variations were designed to simulate a clinical “shoulder”, “chamfer”, and “taper” preparation. A tapered (7°) hardened steel load piston was used to uniaxially load the domes to fracture by inducing radial hoop stress onto the margins. Fractographic post-processing was performed to confirm the fracture mode at cervical margins. Finite element modelling served to analyze the maximum principal stress (σMPS). Weibull statistics were applied on the σMPS data. Results Characteristic fracture forces were 744.3 N for shoulder, 651.1 N for chamfer, and 551.2 N for tapered margin designs. Fracture forces translated into characteristic strength and Weibull moduli of σMPS = 1588.8 MPa (m = 9.2), σMPS = 1616.5 MPa (m = 11.1), and σMPS = 1468.8 MPa (m = 7.6). Fracture initiation was confirmed in the region of dome margins. Significance The margin design had a significant influence on fracture strength, as a significant drop of σMPS at fracture was observed for the taper design. Fractography proved the potential of the test setup to trigger marginal fracture
Keywords: Maximum principal stress; FEM; Fractography; Multilayer zirconia; Hoop strength; Pre-clinical relevance; Crown margin design